COMPETITION IN MICROFINANCE INSTITUTION: A LITERATURE REVIEW - Chaerani Nisa (Dinasti International Journal of Education Management And Social Science, 2020)
This research aims to investigate competition in Microfinance Institution (MFI). MFI is an institution that serves unbankable people through increasing access to finance. Though it faces a challenging situation, many organizations interested in investing in MFI, this condition builds a competitive situation among MFI. Meanwhile, MFI offers diversified products to increase their revenue because they are facing a more intense situation. This research uses a literature survey to find out a journey regarding competition in MFI.